Antibacterial Test of Kedondong Hutan Leaf (Spondias pinnata) Against Salmonella typhi - Rangga, Febby Alvanda; Amarantini, Charis; Budiarso, Tri Yahya (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2024)
Kedondong hutan (Spondias pinnata) is a plant belonging to the Anacardiaceae family, plant that grows a lot in the Sulawesi area, one of which is in the Poso area, Central Sulawesi. The surrounding community uses this plant as a traditional food preparation which is often called the